Mythologization of Image of Marat Kirov in Novel “Sleep and Believe. Blockade Novel” by A. Turgenev - A. M. Lobin (Научный диалог, 2024)
This article presents the results of an analysis of the character system and plot-forming conflicts in the novel by Andrei Turgenev (Vyacheslav Kuritsyn) “Sleep and Believe. Blockade Novel.” The overall state of military-historical prose at the turn of the 20-21 centuries was examined. The main historical myths about the blockade were characterized. An overview of researchers' perspectives on the genre, plot, and poetics of this work was conducted. It was established that A. Turgenev’s novel is part of a postmodern historical discourse, where the metaphysics of the “Petersburg text” intertwines with the most odious myths about the Leningrad blockade (abuses of leadership, arbitrariness of People’s Commissariat of Internal Affairs of the USSR, cannibalism, etc.). Analysis of the text allows us to assert that the central myth and main character of the novel is Marat Kirov, a fictional secretary of the Leningrad Regional Committee. He embodies current historical myths about the blockade, as well as about the real leaders of Leningrad — S.M. Kirov and A.A. Zhdanov. In depicting Kirov, the author widely uses contrast and hyperbolization techniques, as well as numerous references to the “Petersburg text.” As a result, the degree of hyperbolization and demonization fostered by A. Turgenev actualizes the traumatic experience of the entire Soviet history and allows associating the image of the fantastic Marat Kirov with Peter the Great.